Comparison of LDH-Organic/Inorganic Compound Modified Materials as Adsorbents for Heavy Metal Adsorption: Characteristic Structure and Adsorption Mechanism - Normah, Normah; Lesbani, Aldes (Bulletin of Chemical Reaction Engineering & Catalysis, 2024)
This study modified layered double hydroxide (LDH) with organic compounds in hydrochar made from rambutan peels (prepared by hydrothermal method) and polyoxometalate compounds (tipe Keggin K4[ -SiW12O40].nH2O compound and prepared by sol-gel method). The synthesis of modified material was conducted through the coprecipitation method. The material was then applied as an adsorbent for Fe²⁺ ions. The material's properties were analyzed using XRD (X-ray diffraction), FT-IR (Fourier-transform infrared spectroscopy), and BET surface area analysis. The physicochemical characteristics of the modified material, a combination of the pure LDH and hydrochar/polyoxometalate compounds, will influence the adsorption results of Fe²⁺ metal ions. Furthermore, its application as an adsorbent was analyzed through kinetic and isotherm parameters, which were found to follow the pseudo-first-order (PFO) and Freundlich models. The adsorption capacities for NiAl-LDH, NiAl-LDH/Hc (modified with Hc), and NiAl-LDH/POM (modified with POM) materials were 32.789 mg/g, 47.393 mg/g, and 90.091 mg/g, respectively. It can be concluded that the adsorption process occurs via physisorption, forming multilayer adsorbates at the adsorbents active sites. Copyright © 2024 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)